2018
DOI: 10.1108/mhsi-12-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of support groups: a literature review

Abstract: Purpose Purpose: Support groups are a common feature of the mental health support engaged by carers and consumers. The purpose of this paper is to update and consolidate the knowledge and the evidence for the effectiveness of mental health support groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
5
45
0
1
Order By: Relevance
“…However, despite not demonstrating continued effects on symptom-specific outcome measures, aftercare support group attendance may have had transdiagnostic beneficial effects. Worrall et al (2018) found that support groups are effective at reducing symptoms, substance misuse, hospitalizations and use of services, as well as improving social competence and increasing healthy behaviours, self-esteem and perceptions of overall wellbeing. In addition, participants across studies reported many of the same perceived benefits from attending support groups: fostering hope; learning coping strategies; building social and support networks; learning from successful role models; feeling more in control of their situation; and overcoming stigma (Worrall et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite not demonstrating continued effects on symptom-specific outcome measures, aftercare support group attendance may have had transdiagnostic beneficial effects. Worrall et al (2018) found that support groups are effective at reducing symptoms, substance misuse, hospitalizations and use of services, as well as improving social competence and increasing healthy behaviours, self-esteem and perceptions of overall wellbeing. In addition, participants across studies reported many of the same perceived benefits from attending support groups: fostering hope; learning coping strategies; building social and support networks; learning from successful role models; feeling more in control of their situation; and overcoming stigma (Worrall et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As relatives are often the main source of care for the rehabilitating patient, it is essential that they are adequately supported in their role and stressors that may precipitate or exacerbate their own psychological morbidity, must be addressed. It would be worthwhile considering if established support strategies for caregivers of patients with conditions such as strokes, traumatic brain injury, dementia, such as carer support groups (Worrall et al ., ), and psychoeducational interventions to improve caregiving skills and competence (Tang et al ., ) would be effective in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, online support is not necessarily a substitute for face-to-face support groups and in the present study 17% of participants attended a support group but 50% would like to had there been one nearby. This suggests support groups are valued by many people and they have been found to be an important adjunct to psychological support (Worrall et al, 2018).…”
Section: Support From Professionalsmentioning
confidence: 99%